Evaluasi EVALUASI PENERIMAAN MASYARAKAT TERHADAP SISTEM E-TILANG DI KOTA PEKANBARU DALAM PERSPEKTIF KRIMINOLOGI - PURQANI, AZRAJAN; Riky Novarizal (UIR PRESS, 2025)
This research aims to evaluate the public acceptance of the Electronic Traffic Law Enforcement (e-Tilang) system in the city of Pekanbaru from a criminological perspective using Travis Hirschi’s Social Control Theory. The implementation of e-Tilang is intended to reduce traffic violations, prevent bribery, and promote transparency in law enforcement. However, public acceptance plays a crucial role in the effectiveness of this system. Using a qualitative descriptive approach, data were collected through in-depth interviews with traffic violators, the general public, law enforcement officers, and system operators. The findings show that public acceptance of e-Tilang varies. While some support the system for its efficiency and transparency, others face obstacles such as a lack of socialization, limited understanding of procedures, and technological challenges. These factors contribute to public doubts and resistance toward the system. From the perspective of Social Control Theory, the lack of attachment, commitment, involvement, and belief in legal norms correlates with non-compliance. Therefore, the effectiveness of e-Tilang depends not only on its technical implementation but also on its ability to foster social bonds and legal awareness among the public. The study concludes that improvements in public education, accessibility, and responsiveness of the system are necessary for enhancing acceptance and achieving more effective digital law enforcement. Keywords: criminology, ETLE, public acceptance, social control theory